The Impact of Socioeconomic Class and Ethnicity on English Language Teaching/Learning: A Case Study of Five Underprivileged Colombo Schools - Wijesuriya, T. (University of Jaffna, 2025)
This study examines the relationship among socioeconomic class, ethnicity and the teaching/learning of English as a second language in the Sri Lankan school system, based on a case study of GCE O/L classes in five underprivileged schools in the Colombo educational zone. It assesses the ways in which discrimination against underprivileged students is entrenched in systems of teaching and evaluating English, which re-inscribe disadvantage based on class and ethnicity and explores the attitudes which help to hide and/or justify this discrimination. Transcripts of discussions and interviews held with English teachers, principals and students of five underprivileged schools in the Colombo zone, as well as interviews with relevant teacher advisors (ISAs) form the primary information base of this study, which is supplemented by an examination of available statistical data and questions from O/L English papers. Findings include systemic deficiencies of teacher allocation and training, as well as rigid and narrow paper structures which encourage the teaching of a bare minimum of English which, while allowing students to score on the exam does not help them to use the language. Further, that the ideological content of the English papers usually alienates the urban underclass student, and carries the expectation of ‘prior knowledge’ of English in order to do well. Due to practices of teaching English in Sinhala or Tamil, and due to the hierarchies of language in Colombo, many Tamil students in the Sinhala medium schools under study are further disadvantaged. Complicating all this are notions of the purity of language which leads teachers and the system to devalue the language(s) the urban underclass student speaks and blocks more creative and effective ways of language teaching.
Keywords: ELT class; Ethnicity; Education system; Purity of language